The mass society and the elite people in Michael Young's concept - Михайлин, Ігор Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article considers the book «The Rise of Meritocracy» (1958) written by English sociologist and politician Michael Young. The concept of meritocracy, the power of the most worthy, as a promising way of mankind development is revealed. At the same time a threat is possible: the elite people having tasted power tends to leave it for themselves forever and pass an inheritance to their children. International competition forces the English society to return to social mobility — the nomination of the elite individuals from different (and lower) groups.